Assessment of fluid responsiveness: recent advances. Issue 3 (June 2018) - Monnet, Xavier; Teboul, Jean-Louis
Abstract : Purpose of review: In the field of prediction of fluid responsiveness, the most recent studies have focused on validating new tests, on clarifying the limitations of older ones, and better defining their modalities. Recent findings: The limitations of pulse pressure/stroke volume variations are numerous, but recent efforts have been made to overcome these limitations, like in case of low tidal volume ventilation. Following pulse pressure/stroke volume variations, new tests have emerged which assess preload responsiveness by challenging cardiac preload through heart–lung interactions, like during recruitment manoeuvres and end-expiratory/inspiratory occlusions. Given the risk of fluid overload that is inherent to the 'classical' fluid challenge, a 'mini' fluid challenge, made of 100 ml of fluid only, has been developed and investigated in recent studies. The reliability of the passive leg raising test is now well established and the newest publications have mainly aimed at defining several noninvasive estimates of cardiac output that can be monitored to assess its effects. Summary: Research in this field is still very active, such that several indices and tests of fluid responsiveness are now available. They may contribute to reduce excessive fluid balance by avoiding unnecessary fluid administration and, also, by ensuring safe fluid removal.